Development of The Scanometric Method for Caffeine Determination in Pharmaceutical Preparations - Hidayat, Mochammad Amrun; Yunita; Panida, Rahma Riska; Ningsih, Indah Yulia; Kuswandi, Bambang (Jurnal Riset Kimia, 2025)
The caffeine assay can be developed by using sensitive reagents for caffeine detection, such as sodium periodate (NaIO4), acetic acid (CH3COOH), and 3-methyl-2-benzothiazolinone hydrazone (MBTH) inside 96-microwell plate. The addition of caffeine solution could change the color of the reagent from white to deep blue which can be then scanned and quantified by a flatbed scanner and the color image analysis program, known as the scanometric method. Analytical characterization such as linearity, LOD, LOQ, precision, accuracy, and stability of the developed method was established by using caffeine standard. The result of caffeine analysis using the developed method agreed with that of the spectrophotometric method, suggesting that the developed method can be used as an alternative method for caffeine assay in pharmaceutical preparations.